2015
DOI: 10.1186/s12998-015-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of diagnostic ultrasound imaging for musculoskeletal soft tissue pathology of the extremities: a comprehensive review of the literature

Abstract: Musculoskeletal diagnostic ultrasound imaging (MSK-DUSI) has been growing outside the traditional radiology speciality. Increased use of this technology has been reported in several healthcare settings, however an apparent gap in the knowledge of the accuracy of this diagnostic technology indicated a review was warranted. We undertook a structured review of the literature to assess the accuracy of MSK-DUSI for the diagnosis of musculoskeletal soft tissue pathology of the extremities. An electronic search of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 159 publications
(425 reference statements)
0
40
0
1
Order By: Relevance
“…It was later reported that the use of ultrasonography is reliable in diagnosing partial ruptures of Achilles tendon with a sensitivity of 0.94, a specificity of 1.00, and an overall accuracy of 0.95 (Kälebo et al, 1992). More recent studies in humans suggest that musculoskeletal ultrasound has moderate to high diagnostic values in elucidation of Achilles tendinopathy (Henderson et al, 2015). Such data are not yet available in veterinary medicine.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It was later reported that the use of ultrasonography is reliable in diagnosing partial ruptures of Achilles tendon with a sensitivity of 0.94, a specificity of 1.00, and an overall accuracy of 0.95 (Kälebo et al, 1992). More recent studies in humans suggest that musculoskeletal ultrasound has moderate to high diagnostic values in elucidation of Achilles tendinopathy (Henderson et al, 2015). Such data are not yet available in veterinary medicine.…”
Section: Discussionmentioning
confidence: 96%
“…Degenerative injuries may also be secondary to other causes such as systemic disease (Spinella et al, 2010) Ultrasound evaluation has become a valuable and practical tool in assessing the Achilles tendon. It is used frequently in human medicine for diagnostic evaluation and grading of Achilles tendon injuries (Griffith, 2014;Luscombe et al, 2003;Henderson et al, 2015;Royall, 2011;Maffulli et al, 2004). Another advantage of musculoskeletal ultrasound is the possibility to use the contralateral limb as a comparison to evaluate symmetry of the tendon.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that this core or common body of knowledge would change over time. For example, it is possible that there will be an increasing emphasis on MRI and ultrasound imaging modalities [49, 50]. …”
Section: Discussionmentioning
confidence: 99%
“…A CT value of -100 HU is considered a typical clinical soft tissue value [28]. Pulmonary nodules with CT values exceeding this value are generally considered to be solid pulmonary nodules (SPN), which are not difficult to find intraoperatively.…”
Section: Discussionmentioning
confidence: 99%